Developing Anecdote Text Writing Using Animated Videos for Students Class X SMKS PAB-2 Helvetia - Hanum, Afrida; Risnawaty (PT Inovasi Pratama Internasional, 2026)
This study aims to develop a way of writing texts using animated videos, namely, writing anecdotal texts using animated videos that are expected to improve the quality of learning. This research and development uses the ADDIE development procedure. The product of this research was writing anecdotal texts using animated videos for class X SMK. The subjects of the research included material expert validators and media expert validators (design). The steps of this research include analysis, design, development, implementation, and evaluation. The research instruments used in this study includedstudent needs questionnaires, material expert validation, media expert validation, pretest, and posttest tests. The results of this study show that writing anecdotal texts using animated videos uses the ADDIE procedure and obtains validation results with decent qualifications, with a value from material expert validators of 69.5% and media expert validators of 80%. The effectiveness results obtained from the animated video learning media showed good effectiveness results with very good qualifications, and from the pre-test and post-test trials of students showed an increase in the average score from 69.9 to 87.9. The calculation of Normalize Gain (N-Gain) produces an average value of 0.6067 or 60.67%, which is included in the “quite effective” category so that it can be concluded that the product of writing anecdotal text using animated video learning that has been developed in this study is very feasible for students to use in the learning process.